Prevalence and Associated Risk Factors with Early Childhood Caries Among Anganwadi Children of Jaipur City – A Cross-Sectional Study - Sharma, Abhishek; Singh, Mahendra; Tandon, Sandeep; Bahurupi, Yogesh; Chug, Ashi (Journal of Neonatal Surgery, 2025)
Introduction - ECC is defined as the presence of one or more decayed (non-cavitated or cavitated), missing (because of caries), or filled tooth surfaces in any primary tooth in a child 71 months of age or younger. Present study estimated prevalence of early childhood caries (ECC) among Anganwadi children in Jaipur and to assess risk factors associated with early childhood caries among Anganwadi children in Jaipur. Material and methods - Eight Anganwadi centres in Jaipur city were randomly selected for the study. All male and female children enrolled in these eight Anganwadi centres constituted sample for the present study. Early childhood caries was recorded using WHO Oral Health Assessment form 2013. Questionnaire consisted of questions related to oral hygiene practices, diet factors, and socio-behavioral factors was used to explore associated risk factors with ECC. Results - Total 144 children (61 males and 83 females) were enrolled and examined in the study. Prevalence of ECC was found 61.11%. Mean dmfs among study participants was found as 6.02 ± 2.38. More than half of children were on breast feeding (54%). Majority of children (64%) consumed snacks in between snacks. Half of the respondents reported their children’s teeth cleansing frequency as sometimesSnacking in between meals, addition of sugar in baby bottle and no teeth cleaning at night, bottle feeding and feeding in night were associated with risk of ECC. Conclusion -The prevalence of dental caries was higher among the Anganwadi children, indicating the lack of implementation knowledge, underutilization of oral health services and unmet treatment needs..